Beamforming network using switch line phase shifter - M. Ben Omran, Suhil Sharif (2008)
The rapid progresses in radio technology is creating new and improve service at lower cost, which results in increases in air-time usage the number of subscribers. Wireless revenues are currently growing between 20% and 30% per year, and these broad trends are likely to continue for several years. Wireless system designer are faced with a number of challenges one of them is interference. In indoor wireless communication environments, however, reflections from walls, the floor, or the ceiling cause many signal propagation paths and delays, consequently degrading the received signal quality and receiver performance. One of possible solutions is a beamforming technique to direct antenna’s main beam towards a transmitter and to direct nulls towards interference or multipath signal directions, such that incoming signals from reflection paths are suppressed while increasing the antenna gain for a desired signal direction. This project shows the steps of designing beamforming network by implement an active component. It was designed to operate at 2.4GHz for WLAN application. The switch line phase shifter is chosen as way to build a beamforming network. This was designed to provide four different progressive phase shifts -45o, +135o, -135o, +45o that coupled to an antenna array. It is made up from two 900 hybrid coupler, eight phase shifters and eights PIN diode each component is designed and simulated using Agilent ADS software and fabricated on FR4 board. This network is then combined with linear antenna arrays with the aim to produce four independent beams at four different directions. The obtained results shows that 4 beams are generated by rectangular patch antenna array, it is produced half power beam width for each beams about 30o and manage to cover 120o area. Finally, it can be concluded that the objective of this project to design beamforming was achieved.